Mitos sobre la educación musical. - Alva Hurtado, Aarón Alfonso (2023)
The myth, understood as a story transmitted within a society, attempts to explain apparently static ideas, shared by the collective. Likewise, it shapes the actions of that society towards itself and towards the outside world. The objective of this research is to analyze the perceptions of university teachers about the myths of music education. The study responds to a qualitative approach, since it analyzes its natural context, extracting and interpreting perceptible phenomena. Interviews were collected, which described routines and problematic situations, and their meaning in the lives of the participants. A total of 31 myths related to musical education were found. Finally, it is concluded that, even with the appearance of universities and musical careers, a sector of the population continues to consider this profession as something “lesser” compared to other activities, which is why it is necessary to adapt and optimize the relationship between musical teaching programs and the labor field.